2016
DOI: 10.1126/sciimmunol.aaf7471
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific emergence of regulatory and intraepithelial T cells from a clonal T cell precursor

Abstract: Peripheral Foxp3 regulatory T cells (pT) maintain immune homeostasis by controlling potentially harmful effector T cell responses toward dietary and microbial antigens. Although the identity of the T cell receptor (TCR) can impose commitment and functional specialization of T cells, less is known about how TCR identity governs pT development from conventional CD4 T cells. To investigate the extent to which TCR identity dictates pT fate, we used somatic cell nuclear transfer to generate a transnuclear (TN) mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 40 publications
2
76
0
Order By: Relevance
“…As is also the case for CD4 + Tregs 46; 52 , in the setting of limited precursor frequency, iNKT cell lineage choice preferences become more apparent. CD1d-presented ligands are not limiting in the thymus, as shown here and by others 38 ; however particular ligands which might instruct development into NKT1, NKT2, or NKT17 lineages, may be less abundant.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As is also the case for CD4 + Tregs 46; 52 , in the setting of limited precursor frequency, iNKT cell lineage choice preferences become more apparent. CD1d-presented ligands are not limiting in the thymus, as shown here and by others 38 ; however particular ligands which might instruct development into NKT1, NKT2, or NKT17 lineages, may be less abundant.…”
Section: Discussionmentioning
confidence: 86%
“…Somatic cell nuclear transfer is a unique tool used to clone mice from antigen-specific lymphocytes 41; 42; 43; 45; 46 including from iNKT cell nuclei 47 . A previous report of transnuclear iNKT cell mice only used mice that express the Vα14 rearranged TCR and relied on polyclonal Vβ expression 47 .…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, this conversion can be observed among lamina propria regulatory T (T reg ) cells, which subsequently migrate to the intestinal epithelium, lose expression of forkhead box protein P3 (FOXP3) and THPOK and become CD4 + CD8αα + IELs in a microbiota-dependent manner 22 . In further support of this scenario, T cells from mice derived by nuclear transfer from a FOXP3 + T reg cell from the mesenteric lymph node into an enucleated oocyte develop into either lamina propria T reg cells or CD4 + CD8αα + IELs 23 . Thus, CD4 + T cell responses to microbiota antigens may be characterized by plasticity and conversion between the T reg cell and effector IEL programmes 22,23 .…”
Section: Conventional Intestinal Ielsmentioning
confidence: 93%
“…In further support of this scenario, T cells from mice derived by nuclear transfer from a FOXP3 + T reg cell from the mesenteric lymph node into an enucleated oocyte develop into either lamina propria T reg cells or CD4 + CD8αα + IELs 23 . Thus, CD4 + T cell responses to microbiota antigens may be characterized by plasticity and conversion between the T reg cell and effector IEL programmes 22,23 .…”
Section: Conventional Intestinal Ielsmentioning
confidence: 93%
“…CD4-IELs acquire a Th1-like phenotype and are implicated in contributing to the inflammation-mediating damage in celiac disease, ulcerative colitis, and Crohn's disease, but precisely how is unknown 67,68. It was recently shown that somatic cell nuclear transfer of a TCR derived from a lamina propria Treg cell drove not only differentiation into a peripheral Treg fate, but into CD4-IELs as well, suggesting there is some level of shared specificity between them 69. Another fascinating subset of αβ IELs are known as the "natural"IELs.…”
mentioning
confidence: 99%